2022
DOI: 10.5194/acp-22-8819-2022
|View full text |Cite
|
Sign up to set email alerts
|

Contrail formation within cirrus: ICON-LEM simulations of the impact of cirrus cloud properties on contrail formation

Abstract: Abstract. Contrail formation within natural cirrus introduces large perturbations in cirrus ice crystal number concentrations, leading to modifications in cirrus microphysical and optical properties. The number of contrail ice crystals formed in an aircraft plume depends on the atmospheric state as well as aircraft and fuel properties. Our aim is to study contrail formation within cirrus and, in particular, the impact of pre-existing cirrus on the contrail formation processes. We implement a parameterization f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Following the same methodology, Marjani et al (2022) focused on the number concentration and found an increase within a few hundred meters behind the aircraft and below its flight track. In line with airborne observations, Verma and Burkhardt (2022) simulated contrail formation within pre-existing cirrus and found that contrails increased the ice crystal number concentration of cirrus by a few orders of magnitude. Not only the ice number concentration is modified, but also the effective diameter.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Following the same methodology, Marjani et al (2022) focused on the number concentration and found an increase within a few hundred meters behind the aircraft and below its flight track. In line with airborne observations, Verma and Burkhardt (2022) simulated contrail formation within pre-existing cirrus and found that contrails increased the ice crystal number concentration of cirrus by a few orders of magnitude. Not only the ice number concentration is modified, but also the effective diameter.…”
supporting
confidence: 71%
“…If we imagine the scenario in which an in situ origin cloud starts forming heterogeneously by the deposition of water vapor on INPs and an aircraft exhaust jet is introduced, the natural ice particles to be formed would be substituted by the freshly formed contrail affecting severely the resulting microphysical properties. Contrail formation within cirrus can increase the cirrus ice crystal number by a few orders of magnitude (Schröder et al, 2000;Voigt et al, 2017;, in particular if the pre-existing cirrus has high ice water content and the supersaturation is low (Verma and Burkhardt, 2022). In this sense, we can expect an influence of contrail formation and growth on the formation process of in situ origin cirrus at cruise altitudes by an increase in the N and reduction in ED.…”
Section: Relating Ice Cloud Microphysical Properties To the Location ...mentioning
confidence: 98%
“…Recently, many cloud related variables such as precipitation features, cloud vertical structure, cloud sizes, and daily cycles were shown to be improved in storm‐resolving simulations (Stevens et al., 2020) but uncertainties connected with the cloud microphysical schemes remain. Further improvements can be expected if future contrail cirrus studies can utilize the progress in storm‐resolving modeling not only in regional studies (Verma & Burkhardt, 2022) but also on the global scale.…”
Section: Discussionmentioning
confidence: 99%
“…They explore the effects only on thin, mainly in situ origin cirrus, defined as those clouds with geometrical thickness smaller than 2 km. The primary effect of aircraft aerosols is to increase ICNC (Kärcher et al, 2021;Verma & Burkhardt, 2022). This is shown indirectly by studies examining the effect of reducing soot number in aviation fuel and consequently ICNC (e.g., Burkhardt et al, 2018;Voigt et al, 2021).…”
mentioning
confidence: 99%
“…This is shown indirectly by studies examining the effect of reducing soot number in aviation fuel and consequently ICNC (e.g., Burkhardt et al, 2018;Voigt et al, 2021). Verma & Burkhardt (2022) use an LES model to show that contrail cirrus formation within existing cirrus can increase ICNC by a few orders of magnitude, especially in optically thick cirrus but also, to a lesser extent, in relatively thin cirrus.…”
mentioning
confidence: 99%